Pemisahan Emas Pada VGA (Video Graphics Array) Komputer Dengan Metode Leaching Dan Presipitasi - Juliani Dafis; Yusnimar Yusnimar; Drastinawati Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The development of electronics technology is correlated to increasing use of electronic device, it causes a buildup of electronics waste every year. An example is Video Graphics Array (VGA) Computer still has the precious metals components. In this research, gold separation process of VGA computer has been done by using variation ratio samples : HNO3 solvent (1: 3; 1: 6; 1: 9) and two precipitants NaHSO3 and H2C2O4. Initially VGA cut into size from 5-10 mm, then it was leaching by HNO3 solvent at 70 ℃ for 1 hour. Afterwards filtrate is separated from residual sludge. Residual sludge was leaching using Aqua regia at 70 ℃ for 30 minutes to dissolve gold. Then, Au filtrate is obtained are diluted using Aqua DM until the volume 50 mL. The concentration Au is analyzed by AAS (Atomic Absorption Spectrophotometer). In the precipitation process NaHSO3 and H2C2O4 were applied in order to get Au solid. Result Au content of VGA is 76.2 ppm. For 5 gram amount of sample is obtained 1.07 grams Au solid using NaHSO3 as a precipitant.Keywords: Au, Computer VGA, leaching, precipitant,